Mini Review Protein Value and The Importance of Energy Ratio (Case study on Oreochromis Niloticus Diet) - Haetami, Kiki; Harmonis, Jacky Abdul Aziz; Putri, Naila Jasmine Alifah; Nusyaibah, Kei Aqila; Putri, Nayla Chalisa; Syahputra, Moch Risfi; Aulia, Rio Farhan; Kusmana, Naufal Rizky (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Nile tilapia (Oreochromis niloticus) is one of the most widely fish species in aquaculture due to its fast growth, high adaptability, and economic value. Factors influencing the success of tilapia is the provision of nutritionally balanced feed, particularly regarding the type and level of dietary protein. This review aims to explain several biochemical aspects of the type and level of protein in feed as a support for growth efficiency, a case study on Nile tilapia (Oreochromis niloticus). Protein is an important component in metabolic processes. Several biochemical perspectives, including protein metabolism and digestive enzyme activity manifested in growth. Various studies show that optimal protein levels in feed can enhance the growth efficiency of Nile tilapia and growth parameters Specific Growth Rate (SGR). This study concludes that protein-based feed formulation needs to also consider the presence of other energy source contents such as carbohydrates in tilapia to achieve optimal aquaculture efficiency. This is because sufficient carbohydrates help protein as an energy source, thus protein will maximize to support growth, weight, and meat content in Nile tilapia. The most suitable protein content in tilapia fish based on several studies is 35-40% protein to prevent excess protein, while the carbohydrate content is 10-50% to support the growth of tilapia.